Psychoactive substances users’ health conditions - Michele Mandagará de Oliveira; Karine Langmantel Silveira; Paola de Oliveira Camargo; Andreza Erdmann Furtado; Tais Alves Farias; Camila Feijo Luft (Revista de Enfermagem da Universidade Federal de Santa Maria, 2017)
Aim: to analyze the association between the abusive use of psychoactive substances and infectious and/ or contagious diseases, chronic non-communicable diseases and minor psychiatric disorders. Methodology: it is a Cross sectional study, with a sample of 505 users, of whom 136 were crack users. Chi-square tests were used to verify proportional differences and, as a measure of association, the prevalence ratio was used. Results: the majority of the interviewees reported being in good health, also reporting that they did not have diseases. The results also showed that there was an association between the use of crack and sexually transmitted infections, the most prevalent being acquired immunodeficiency syndrome followed by hepatitis C. Substance use may also be related to the onset of minor psychiatric disorders. Conclusions: from this study, it is paramount to reflect upon public policies for this population, paying attention to health issues and needs, aiming an integral care.